2017
DOI: 10.1016/j.ecoenv.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective metabolism of triadimefon and its chiral metabolite triadimenol in lizards

Abstract: Chinese lizards (Eremias argus) were exposed to separated R-(-)-triadimefon, S-(+)-triadimefon and racemic triadimefon to evaluate enantioselective accumulation of triadimefon. After single oral administration of R-(-)-triadimefon, S-(+)-triadimefon and racemic triadimefon, the time-concentration curves in different tissues were found to be different. Triadimefon enantiomers crossed the blood-brain barrier and brain is a main target organ. The residues of triadimefon enantiomers in fat were highest after 24h i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Four bitertanol stereoisomers also had different environmental behaviors and biological effects. , (−)-Hexaconazole showed 6-fold more toxicity than (+)-hexaconazole against Scenedesmus obliquus . Triadimefon and its chiral metabolite triadimenol showed enantioselective metabolism in lizards . Li et al found that (−)-fenbuconazole was preferentially degraded in soil, and the metabolites of fenbuconazole also exhibited significant enantioselectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Four bitertanol stereoisomers also had different environmental behaviors and biological effects. , (−)-Hexaconazole showed 6-fold more toxicity than (+)-hexaconazole against Scenedesmus obliquus . Triadimefon and its chiral metabolite triadimenol showed enantioselective metabolism in lizards . Li et al found that (−)-fenbuconazole was preferentially degraded in soil, and the metabolites of fenbuconazole also exhibited significant enantioselectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic rates of RS-TDN and RR-TDN were more rapid than that of SR-TDN and SS-TDN, respectively. S-TDF was absorbed faster than R-TDF, and R-TDF was easily metabolism to TDN in lizards [51]. However, in vitro in Rainbow trout (Oncorhynchus mykiss), S-TDF was more easily transformed to triadimenol than R-TDF [53], which illustrated that species differences in stereo-selective metabolism of triadimefon.…”
Section: Metabolism and Eliminationmentioning
confidence: 98%
“…As for other vertebrate taxa, toxins have variable effects on BBB integrity, and in some cases, can cross the BBB. For example, the fungicide triadimefon crosses the BBB of the Chinese lizard (Eremias argus), entering the neural tissue of the brain [134]. Cadmium crosses the BBB and alters glial structure in the brain of the Italian wall lizard Podarcis siculus [133].…”
Section: Factors Altering Reptilian Blood-brain Barrier Functionmentioning
confidence: 99%